Effects of alcohol abuse and depression on olfactory treshold - Çalıyurt, Okan; Küçüktürk, Ertuğrul; Karaşin, Engin; Abay, Ercan (Journal of Dependence, 2000)
Object: There are numerous studies showed that biological cahanges occur with effects and consequences of psychiatric disorders. Depression and alcohol abuse negatively change the brain blood flow and make damage in the central nervous system. To determine the potential effects of these two disorders on olfactory areas and connection pathways aimed in this study.Method: Olfactory treshold changes measured by Zwaardemaker olfactometry apparatus. Measurement made in both two nostrils seperately. Data achieved from depression and alocohol abuse groups compared with normal control group.Result: There was an elevation found in olfactory tresholds of both alcohol and depression patients. In alcohol group the elevation was the highest. There was no lateralisation found except two alcohol abused patients.Discussion: Olfactory treshold elevations showed in this study. By the consequenses of brain damage and central nervous system changes in depression and alcohol abuse patients olfactory treshold seems to change and makes difficulties on olfaction.Key words: Alcohol abuse, depression, olfactory treshold
Keywords: Alcohol abuse; depression; olfactory treshold